2022
DOI: 10.17711/sm.0185-3325.2022.008
|View full text |Cite
|
Sign up to set email alerts
|

Validity of the classification of emergency service requests related to suicidal behavior

Abstract: Introduction. Suicide attempts are the most predictive risk factor for suicide deaths. Most people who attempt suicide receive care from out-of-hospital Emergency Services (OES), where these requests are managed and classified. Objective. Validate the Emergency Coordination Center (ECC) classification for the detection of suicidal behavior requests. Method. A descriptive, cross-sectional study of requests to the ECC of Málaga (Spain) during 2013 and 2014 was conducted. To classify the requests, the authors con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Although some articles based on the coding and classification of suicidal behavior cases have been questioned for their lack of reliability and consequently under- or over-recording of cases ( 39 ), in our study, we applied strict criteria to identify the calls as suicidal behavior, since we took into account both the clinical judgment of the out-of-hospital emergency doctor attending the patient in situ and the criteria of the operator responding to the telephone call at the 061 ECC. However, we are aware that a study carried out in our setting concluded that the classification system used in the 061 ECC has a sensitivity of 44.8% for detecting cases of suicidal behavior ( 16 ). Following on from this reflection, Anderson et al ( 40 ) state that little training is available on how visits for suicidal behavior should be documented and that research that relies on international disease classification codes included in medical records to study suicide sometimes significantly underestimates cases of suicide attempts and suicidal ideation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although some articles based on the coding and classification of suicidal behavior cases have been questioned for their lack of reliability and consequently under- or over-recording of cases ( 39 ), in our study, we applied strict criteria to identify the calls as suicidal behavior, since we took into account both the clinical judgment of the out-of-hospital emergency doctor attending the patient in situ and the criteria of the operator responding to the telephone call at the 061 ECC. However, we are aware that a study carried out in our setting concluded that the classification system used in the 061 ECC has a sensitivity of 44.8% for detecting cases of suicidal behavior ( 16 ). Following on from this reflection, Anderson et al ( 40 ) state that little training is available on how visits for suicidal behavior should be documented and that research that relies on international disease classification codes included in medical records to study suicide sometimes significantly underestimates cases of suicide attempts and suicidal ideation.…”
Section: Discussionmentioning
confidence: 99%
“…Our line of research has focused on studies of suicidal behavioral calls to out-of-hospital emergency services settings only ( 9 , 15 , 16 ). There are also several studies focused on this population in the hospital emergency setting ( 17 19 ).…”
Section: Introductionmentioning
confidence: 99%